Pelestarian Ekosistem Mangrove Melalui Pemanfaatan Jeruju (Acanthus Ilicifolius) sebagai Makanan Ringan Alternatif - Muhammad Romdonul Hakim; Abdul Rahman; Fajar Alhabsi; Vicky Rizky Affandi Katili; Mustasim Mustasim (Politeknik Kelautan dan Perikanan Sorong, 2021)
Abstract: Jeruju has so far been underutilized and even considered shrubs so that its habitat is often threatened. The purpose of this community service activity is to educate the public that jeruju can be processed into chips with high economic value, so it is important to maintain its sustainability. This activity was carried out by inviting 10 women from Babakan Village, Pangandaran Regency to attend training on making jeruju chips. The results of monitoring and evaluation showed that during the practice of making jeruju chips, all the trainees could practice them carefully without showing any difficulties.